Efektivitas Model Pembelajaran Kooperatif Tipe Stad Di Smp Muhammadiyah 3 Tanjung Sari Medan - Matondang, Ahmad Barkah (EL-EMIR Institute, 2024)
This study aims to examine the effectiveness of the implementation of the Student Teams Achievement Division (STAD) cooperative learning model in improving student learning outcomes at SMP Muhammadiyah 3 Tanjung Sari Medan. This study was conducted to provide a clear picture of the comparison of the effectiveness of the STAD learning model with conventional learning methods that have been applied so far. This study used an experimental method with a two group pre-test post-test design. The population in this study were all 7th grade students of SMP Muhammadiyah 3 Tanjung Sari Medan, while the sample was selected randomly involving two groups, namely the experimental group using the STAD learning model and the control group using the conventional learning model. The data collection technique was carried out through a written test designed to measure the level of student understanding of the subject matter given. Before and after treatment, both groups were given a test to determine changes in learning outcomes. The data obtained were analyzed using a t-test to test the research hypothesis. The results showed that the STAD learning model was more effective in improving student learning outcomes compared to the conventional learning model. This is proven by the results of the t-test which shows that the t-value (3.392) is greater than the t-table (2.000) at a certain level of significance. Thus, the application of the STAD learning model has been proven to be able to increase student involvement in the learning process, strengthen understanding of the material, and encourage better learning outcomes. This study provides recommendations so that the STAD learning model can be applied more widely in various schools as an effort to improve the quality of education. Keywords: STAD, Learning Model, Cooperative